A “Comparison of the Efficiency of Hydraulic Vibro Pile Hammer and Diesel Hammer Based on Time and Cost Productivity Analysis in the Coastal Protection Project of Cilacap Regency.”: Perbedaan Efisiensi Alat Pancang Hydraulic Vibro Pile Hammer dan Diesel Hammer Berdasarkan Analisis Produktivitas Waktu dan Biaya pada Proyek Pengaman Pantai Kabupaten Cilacap - Milenia, Iva Arista; Putri Anggi Permata Suwandi; Ikhwanudin; Edwin Medy Suseno; Achmad Meydo Pratama (SAINTIS Jurnal ilmu-ilmu eksakta, 2025)
Abstract. Coastal areas that are vulnerable to abrasion caused by ocean waves require coastal protection structures, commonly known as revetments. One of the coastal areas affected by abrasion is the shoreline in Cilacap Regency. In the Coastal Protection Project of Cilacap Regency, the type of revetment used is Flat Concrete Sheet Pile (FCSP). This study aims to analyze the efficiency level of two piling equipment, Hydraulic Vibro Pile Hammer and Diesel Hammer, based on their productivity values in driving FCSP. The results of the analysis show that the Hydraulic Vibro Pile Hammer has a productivity of 16.83 m/hour with a working duration of 18 days and a cost of IDR 85,050,000. Meanwhile, the Diesel Hammer demonstrates higher performance with a productivity of 20.79 m/hour, a total working duration of 14.57 days, and a cost of IDR 52,524,850. Thus, the Diesel Hammer is considered more efficient in terms of both time and cost compared to the Hydraulic Vibro Pile Hammer. The study also identifies that equipment condition and external factors significantly influence the productivity level of the piling equipment.